2019
DOI: 10.18502/jthc.v14i2.1371
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Short-Term Results between Patients Undergoing Coronary Artery Bypass Graft with a Stent-Placement History and Patients Undergoing Primary Coronary Artery Surgery

Abstract: Background: Percutaneous coronary intervention (PCI) has become the first-choice treatment strategy the world over for patients with chronic coronary artery disorders. This study compared the effects of previous PCI procedures on the short-term postoperative results of coronary artery bypass graft surgery (CABG). Methodsː This cross-sectional analytical study recruited 220 patients who underwent CABG in Afshar Hospital in the Iranian city of Yazd between March 2009 and February 2013. The mean postoperati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 20 publications
0
3
0
2
Order By: Relevance
“…Demographic factors, CAD risk factors, comorbidities, coronary lesion characteristics, and perioperative characteristics were adjusted varyingly in most of the included studies, while nine studies with nonsignificant results on univariate analysis were also included. 7 , 12 , 15 , 20 , 28 , 29 , 33 , 36 , 37 Fifteen multivariate studies excluded patients with acute PCI failure. 8 , 9 , 11 , 13 , 17 19 , 21 , 23 , 25 , 27 , 34 , 35 , 38 , 41 Because four studies reported outcomes according to the times of prior PCI 11 , 17 , 35 , 41 or the duration of the gap between PCI and CABG, 21 multiple datasets were considered for these studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Demographic factors, CAD risk factors, comorbidities, coronary lesion characteristics, and perioperative characteristics were adjusted varyingly in most of the included studies, while nine studies with nonsignificant results on univariate analysis were also included. 7 , 12 , 15 , 20 , 28 , 29 , 33 , 36 , 37 Fifteen multivariate studies excluded patients with acute PCI failure. 8 , 9 , 11 , 13 , 17 19 , 21 , 23 , 25 , 27 , 34 , 35 , 38 , 41 Because four studies reported outcomes according to the times of prior PCI 11 , 17 , 35 , 41 or the duration of the gap between PCI and CABG, 21 multiple datasets were considered for these studies.…”
Section: Resultsmentioning
confidence: 99%
“… 6 However, previous studies evaluating the association between prior PCI and prognosis after CABG have shown inconsistent results. 7 42 Although a number of meta-analyses have been performed on this topic, the results of these studies were also inconsistent. Two early meta-analyses including 9 and 14 studies, respectively, concluded that prior PCI may be related to a higher incidence of postoperative mortality within 1 month, but not to midterm mortality up to 5 years after CABG.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Характеристики и исходная терапия больных ИБС, перенесших КШ, с предшествующим ЧКВ с СКА или без такового Table 1 В литературе приводятся противоречивые данные о частоте госпитальных осложнений КШ среди пациентов с предшествующей коронарной ангиопластикой. Так, в исследованиях [1,11] не выявлено различий в госпитальной летальности и в частоте ССС после КШ между группами пациентов с предшествующим ЧКВ и без такового. Вместе с тем другие авторы указывают на более высокие показатели госпитальной смертности и частоты ССС среди пациентов с предшествующим ЧКВ с СКА [12][13][14].…”
Section: Discussionunclassified
“…Однако до настоящего времени остается недостаточно ясным, оказывают ли неблагоприятное влияние на ближайшие и отдаленные исходы КШ ранее выполненные ЧКВ и СКА. Результаты ранее проведенных исследований противоречивы [1][2][3].…”
Section: Original Articleunclassified